Change of ionized calcium level in the first 48 hours of age of preterm newborns administered with two different dosages of intravenous calcium gluconate - Anton Wibowo; Dedi Rachmadi Sambas; Abdurachman Sukadi (Paediatrica Indonesiana, 2010)
Background Physiologically, serum calcium level declines till nadirin a few hours after birth and continues for 24-48 hours. No studyperformed in order to know the alteration ofionized calcium levelof newborn in the first 48 hours of age. The sick newborn musthave parenteral calcium to avoid hypocalcemia but there is stillno agreement about the dose.Objective To determine the change of ionized calcium level inthe first 48 hours of age of preterm newborns administered withperipheral drip intravenous 10% calcium gluconate of2.6 mIJkg/day and 5 mUkg/day.Methods An open labeled randomized controlled clinical trialwas performed between April and June 2009. After birth bloodspecimen of preterms was obtained for leukocyte, platelet,magnesium, phosphorous, and ionized calcium measurements.Subjects received either 2.6 mL/kg/day or 5 mL/kg/day ofperipheral drip intravenous 10% calcium gluconate immediatelyafter birth for 48 hours. Blood specimens was obtained again on48 hours of age for ionized calcium. This study were analyzedusing repeated measures analysis of varians.Results Forty preterm newborns (20 subjects each group) wereanalyzed. There was no statistical difference between bothdoses (Factor-A) on 48 hours ionized calcium level (P=0.33)and ionized calcium level alteration based on time (Factor-B)(P=0.20). Interaction between both factors was significantlydifferent (P=0.035).Conclusion Ionized calcium level in 48 hours of age of pretermnewborn administered with both doses of 10% calcium gluconate isnot different but dose of2.6 mL/kg/day yields physiologic alterationof ionized calcium level compared with 5 mL/kg/day.